Creating Value in Non-Profit Sports Organizations: An Analysis of the DART Model and Its Performance Implications - Jorge Iván Brand Ortíz; Silvana Janeth Correa Henao; Laura Cristina Henao Colorado; Alejandro Valencia-Arias (European Journal of Investigation in Health, Psychology and Education, 2023)
This study aims to analyze the impact of value creation and cocreation, as measured by the dialogue, access, risk assessment, and transparency (DART) model, on the performance of non-profit sports organizations (NPSOs). To assess this impact, the authors analyzed data collected from sports and administration managers of NPSOs, specifically Colombian amateur soccer clubs. The study used partial-least-squares structural-equation modeling (PLS-SEM) with constructs of the reflexive-formative type. The results indicate that value creation has a positive impact on the performance of NPSOs through the mediating effect of value cocreation. Despite the limitations of this study, including the limited research on the relationship between value creation and cocreation and NPSO performance in Colombia, the findings contribute to the understanding of the mediating effect of cocreation. The authors found that cocreation mainly affects the sport, customers/members, communication and image, finance, and organization dimensions of NPSOs in developing countries. This study draws attention to the potential benefits of cocreation for NPSOs and emphasizes the importance of creating value in this context. The study concludes that further studies on the constructs proposed in this research would help to understand the phenomenon of innovation and its impact on NPSOs. Overall, this study provides valuable insights for managers and policymakers in NPSOs—especially in developing countries—on the importance of value cocreation in improving their performance.